2016
DOI: 10.1111/jpc.13277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an E‐learning resource on approach to the first unprovoked seizure

Abstract: The E-learning resource has been validated as a useful educational resource regarding the first afebrile unprovoked seizure for paediatricians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Studies included those with externally validated questionnaires to measure students' performance (e.g., Kemper, 2017;Willman et al, 2018) and studies which had validated their own questionnaires (e.g., Heuberger et al, 2019;Schulz-Quach et al, 2018). Some questionnaires were specific to their subject content, such as stroke assessment (Gorchs-Molist et al, 2020), drug dispensing (dos Reis et al, 2019), and seizure management (Le Marne et al, 2016) and others measured self-directed learning readiness (Gagnon et al, 2015;Reviriego et al, 2014). Finally, the study by Kemper (2017) focused on questionnaires specific to measuring mindfulness (refer to Table 3) but did not measure the long-term impact on the participants.…”
Section: Performance Measures: Assessment Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Studies included those with externally validated questionnaires to measure students' performance (e.g., Kemper, 2017;Willman et al, 2018) and studies which had validated their own questionnaires (e.g., Heuberger et al, 2019;Schulz-Quach et al, 2018). Some questionnaires were specific to their subject content, such as stroke assessment (Gorchs-Molist et al, 2020), drug dispensing (dos Reis et al, 2019), and seizure management (Le Marne et al, 2016) and others measured self-directed learning readiness (Gagnon et al, 2015;Reviriego et al, 2014). Finally, the study by Kemper (2017) focused on questionnaires specific to measuring mindfulness (refer to Table 3) but did not measure the long-term impact on the participants.…”
Section: Performance Measures: Assessment Of Knowledgementioning
confidence: 99%
“…Gorchs-Molist et al (2020) reported multiple follow-up periods, including after 1-2 years (71% response rate) and 3-4 years (91% response rate). Several studies identified the need to follow-up participants but could not undertake this process (Le Marne et al, 2016;Liaw et al, 2016;Simonsen et al, 2014;Uden-Holman et al, 2014).…”
Section: Performance Measures: Long-term or Follow-upmentioning
confidence: 99%
“…Studies included those with externally validated questionnaires to measure students' performance (e.g., Kemper, 2017;Willman et al, 2018) and studies which had validated their own questionnaires (e.g., Heuberger et al, 2019;Schulz-Quach et al, 2018). Some questionnaires were specific to their subject content, such as stroke assessment (Gorchs-Molist et al, 2020), drug dispensing (dos Reis et al, 2019), and seizure management (Le Marne et al, 2016) and others measured self-directed learning readiness (Gagnon et al, 2015;Reviriego et al, 2014). Finally, the study by Kemper (2017) focused on questionnaires specific to measuring mindfulness (refer to Table 3) but did not measure the long-term impact on the participants.…”
Section: Performance Measures: Assessment Of Knowledgementioning
confidence: 99%
“…Gorchs-Molist et al (2020) reported multiple follow-up periods, including after 1-2 years (71% response rate) and 3-4 years (91% response rate). Several studies identified the need to follow-up participants but could not undertake this process (Le Marne et al, 2016;Liaw et al, 2016;Simonsen et al, 2014;Uden-Holman et al, 2014).…”
Section: Performance Measures: Long-term or Follow-upmentioning
confidence: 99%